Logistics Centers as Determinants Influencing the Development of the Economic Potential of a Region - Leszek SZCZUPAK (Communications of International Proceedings, 2021)
The location of the logistics centre has a significant influence on the development of a region and determines the directions of its development. Another extremely important element is the activity of local governments, which through their actions may affect the investment attractiveness of a given region. The location of a logistics centre raises the economic potential of a given region influencing at the same time the improvement of living conditions of its citizens.
Keywords: Logistics Centres; Regional Development; Logistics Infrastructure